2021
DOI: 10.1186/s41182-021-00343-x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of deworming medication and its associated factors among pregnant married women in 26 sub-Saharan African countries: a multi-country analysis

Abstract: Background Deworming is one of the strategies to reduce the burden of anemia among pregnant women. Globally, pregnant women in sub-Saharan Africa are more affected by anemia. Therefore, this study examined both the coverage and demographic, socioeconomic, and women empowerment-related factors associated with the utilization of deworming medication among pregnant married women in sub-Saharan Africa. Methods We used data from the most recent Demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 44 publications
(56 reference statements)
3
23
3
Order By: Relevance
“…This finding is in line with a prior study in Uganda [ 10 ]. The possible justification might be that older women have higher income status and better educational and carrier achievement than adolescents [ 46 48 ]. Older women are usually experienced in the utilization maternal health services, proactive and they usually emphasize on activities of prevention of diseases [ 46 , 48 , 49 ] and are more likely to have an HIV-test [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with a prior study in Uganda [ 10 ]. The possible justification might be that older women have higher income status and better educational and carrier achievement than adolescents [ 46 48 ]. Older women are usually experienced in the utilization maternal health services, proactive and they usually emphasize on activities of prevention of diseases [ 46 , 48 , 49 ] and are more likely to have an HIV-test [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women who have Anti Natal Care (ANC) visits were more likely to take their child deworming medication than women with no ANC visit. A study in 26 sub-Saharan African countries for utilization of deworming for pregnant mothers showed that having ANC visits has a positive association with utilization of deworming medication [ 41 ]. So as if women utilized a deworming medication for themselves because of havening ANC follow up, they already know the advantage and expected to use it for their child.…”
Section: Discussionmentioning
confidence: 99%
“…It is in line with a study in India [ 17 ] and supported by a study done in Nigeria which showed that utilization of health care can be improved when maternal media exposure increases [ 1 ]. Moreover, a study in 26 sub-Saharan African countries showed that women who have media exposure had higher odds of the utilization of deworming for themselves [ 41 ]. Exposure to media could have a tremendous role in increasing awareness and knowledge for mothers and the dissemination of health-related information [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ethiopia, a systematic review and meta-analysis study reported a pooled prevalence of intestinal parasites among pregnant women of 29% [ 3 ]. Pregnant women with intestinal parasite infections are more likely to have maternal problems and poor perinatal outcomes, such as anemia, low birth weight, and perinatal mortality [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%